2005
DOI: 10.1371/journal.pcbi.0010042
|View full text |Cite
|
Sign up to set email alerts
|

The Human Connectome: A Structural Description of the Human Brain

Abstract: The connection matrix of the human brain (the human “connectome”) represents an indispensable foundation for basic and applied neurobiological research. However, the network of anatomical connections linking the neuronal elements of the human brain is still largely unknown. While some databases or collations of large-scale anatomical connection patterns exist for other mammalian species, there is currently no connection matrix of the human brain, nor is there a coordinated research effort to collect, archive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
2,222
0
26

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 2,940 publications
(2,321 citation statements)
references
References 79 publications
10
2,222
0
26
Order By: Relevance
“…Understanding the structural basis of functional connectivity patterns requires a comprehensive map of structural connection of the human brain (the human connectome (Hagmann, 2005;Sporns et al, 2005)). We have just seen that advances in diffusion imaging and tractography methods permit the non-invasive mapping of white matter cortico-cortical and cortico-subcortical projections at high spatial resolution.…”
Section: From Tracts To Network 231 Past and Current State Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the structural basis of functional connectivity patterns requires a comprehensive map of structural connection of the human brain (the human connectome (Hagmann, 2005;Sporns et al, 2005)). We have just seen that advances in diffusion imaging and tractography methods permit the non-invasive mapping of white matter cortico-cortical and cortico-subcortical projections at high spatial resolution.…”
Section: From Tracts To Network 231 Past and Current State Of Thementioning
confidence: 99%
“…The perspective of collecting large amounts of connectional data combined with the understanding that the fundamental properties of the brain result from large-scale network topology has led two researchers, at that time independent, to realize the prime importance of this emerging technology, and to conceptualize in 2005 the notion of "connectome" and its related science "connectomics" (Hagmann, 2005;Sporns et al, 2005). In complete analogy to the word "genome", this new "-ome" emphasizes to the notion that the brain is one large and unique structural entity: a network made of neural connections (edges) and neural units (nodes).…”
Section: Introductionmentioning
confidence: 99%
“…For the reconstruction of complete cellular wiring diagrams ("connectomes" [8][9] ) assuring reconstruction reliability is even more difficult because the morphologies of all neurons, not only those of a small subset, have to be extracted. This may eventually be possible at light-microscopic resolution by staining all neurons with a sufficient number of distinguishable colors 7,9 but otherwise requires imaging at a resolution high enough to follow all neurites in densely packed neuropil (discussed in 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…2011); also known and for the first time described as the human connectome (Sporns et al. 2005). Studies using graph analysis have shown that the human brain demonstrates small‐world properties, meaning that the network has a highly clustered local connectivity (greater than in a random network) and that there is a shorter path length (in terms of shortest distance) between brain regions than would be expected in a regular network (Watts and Strogatz 1998; Achard et al.…”
Section: Introductionmentioning
confidence: 99%